Galaxies, galaxies! - Gibbons, Gail. (New York : Holiday House, 2007)
An illustrated introduction to galaxies, discussing their physical characteristics and the methods used to observe them.
Horn Book.
School Library Journal.
Wilson's Children.
5.0
K-3
Keywords: Galaxies -- Juvenile literature; Astronomy; Galaxies; Astronomy; Galaxies